2012 9th Annual Conference on Wireless on-Demand Network Systems and Services (WONS) 2012
DOI: 10.1109/wons.2012.6152239
|View full text |Cite
|
Sign up to set email alerts
|

The effect of variable wake up time on the utilization of sleep modes in femtocell mobile access networks

Abstract: Abstract-Femtocells are considered as an enabler for low power, high bit rate future mobile access networks. In this study, we look at them as a technology to cover an area with a high bit rate connectivity. From the evaluation it is clear that sleep modes are imperative to maximise the energy efficiency of the mobile access network. We evaluate the power reduction and wake up time of different sleep modes and apply them to the model in order to evaluate the influence of the power consumption of the mobile acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Energy-efficient cell breathing and BS switching-off algorithms are an 27 important tool for energy reduction in cellular networks. In this paper, an energy-efficient 28 cell breathing and offloading mechanism in both macrocellular and heterogeneous net- 29 works is studied.…”
mentioning
confidence: 99%
“…Energy-efficient cell breathing and BS switching-off algorithms are an 27 important tool for energy reduction in cellular networks. In this paper, an energy-efficient 28 cell breathing and offloading mechanism in both macrocellular and heterogeneous net- 29 works is studied.…”
mentioning
confidence: 99%
“…The instantaneous power of a sleeping RRH P S thus falls to zero based on Equation (1) because the model given in [9] does not consider the power consumption from the backhaul connection and the basic processing unit. Therefore, P S is modelled according to [40], which is 15% of P B at zero loads. It is also suggested that the wake-up time is modelled.…”
Section: F Power Consumption Modelmentioning
confidence: 99%
“…It is also suggested that the wake-up time is modelled. Since only the RF and PA modules have to be deactivated for a sleep mode, the wake-up time is chosen to be 0.5 seconds as given in [40]. With the power consumption of a RRH modelled, the equivalent instantaneous area power consumption of a C-RAN, P N t considered in a period of time τ, can be calculated as…”
Section: F Power Consumption Modelmentioning
confidence: 99%
“…Furthermore, utilizing sleep mode technology in small cells has also been received much attention recently. [11] models the power consumption in femtocell networks and gains 24% reduction by introducing sleep mode whereas [12] studies the effect of variable wake up time on the utilization of sleep modes. To realize idle conditions in hardware components, [3] obtains 13-56% power savings by different strategies based on mixed voice and data traffic.…”
Section: Introductionmentioning
confidence: 99%